(untitled) (Baltic Journal of Sport and Health Sciences, 2015)
Background. In the modern world, people are short of time for physical and spiritual education, which may lead to major health problems. Due to passive lifestyle, many of them have a poor body composition, impaired circulation and reduced flexibility, which may contribute to physical disorders and susceptibility to chronic diseases (Chen, Tseng, Ting, & Huang, 2007). Hypothesis: lifestyle of yoga practitioners is healthier and health evaluation is better compared to those of non- practitioners. The aims of the research were to asses and compare the features of lifestyle and health evaluation of yoga practitioners and non-practitioners. Methods. The study included middle-aged participants (from 35 to 55 years). A total of 193 people were evaluated, 86 of them were practising yoga. Among these participants, 63 were women, 23 – men. The other 107 did not practise yoga, 58 of them were women, 43 – men. The questionnaire of the lifestyle of Lithuanian adults was used (Grabauskas, Klumbienė, & Petkevičienė, 2011). Results. The analysis of the results confirmed the hypothesis proposed at the beginning of the work. Yoga practitioners’ nutrition, physical activity, addictions and evaluation of their health was better than those of non- practitioners. Conclusion. Yoga practitioners have healthier lifestyle habits, they consume less animal fat, eat more fruits, cereals and cereal-based products. In addition, they are more physically active than non- practitioners, both men and women often exercise alone or in group practice sessions and without yoga they have more kinds of physical activity. A lower prevalence of addictions was observed among them; none of them smoked and they had a lower intake of alcohol beverages compared to yoga non-practitioners. Yoga practitioners are healthier and have a better value of their health and the quality of life. Keywords: yoga, lifestyle, health assessment.